Strategi Peningkatan Aktivitas Remaja Masjid Di Era Digital: Analisis SWOT Pada Ikatan Remaja Masjid Kabupaten Bangka - Agung Priyono; Hadarah Rajab; Rada (Al-Qolamuna: Journal Komunikasi dan Penyiaran Islam, 2025)
This study explores the role of mosque youth in enhancing religious activities in the digital era, particularly in the utilization of digital technology by the Youth Mosque Association (Irmas) in Bangka Regency. The current phenomenon indicates that the existence and participation of youth in mosque activities are still not optimal. The aim of this research is to analyze the strengths, weaknesses, opportunities, and threats (SWOT) that influence Irmas activities, as well as to formulate strategies for improvement. A qualitative approach with a descriptive method was used. Data were collected through observation, documentation, and interviews with several Irmas in Bangka Regency, including Irmas Al-Ittihaad Sungailiat, PRM Fathurrahman Kimak Merawang, PRM Nurul Iman Payabenua Mendo Barat, and Irmas Nurul Huda Gunung Muda Belinyu. The findings reveal supporting factors such as village culture, funding, mosque facilities, members’ backgrounds, and their enthusiasm. Meanwhile, inhibiting factors include the busyness of some administrators, declining motivation, and the distance to the mosque. The proposed strategies include continuous youth development through mosques, improving the quantity and quality of members, strengthening collaboration with mosque management (takmir), and utilizing digital technology to enhance the visibility and effectiveness of mosque youth activities. Abstrak Penelitian ini membahas peran remaja masjid dalam meningkatkan aktivitas keagamaan di era digital, khususnya dalam pemanfaatan teknologi digital oleh Ikatan Remaja Masjid (Irmas) di Kabupaten Bangka. Fenomena yang terjadi menunjukkan bahwa eksistensi dan partisipasi remaja dalam kegiatan masjid masih belum optimal. Tujuan dari penelitian ini adalah untuk menganalisis faktor kekuatan, kelemahan, peluang, dan ancaman (SWOT) yang memengaruhi aktivitas Irmas, serta merumuskan strategi peningkatannya. Menggunakan pendekatan kualitatif dengan metode deskriptif. Data dikumpulkan melalui observasi, dokumentasi, dan wawancara terhadap beberapa Irmas di Kabupaten Bangka, seperti Irmas Al-Ittihaad Sungailiat, PRM Fathurrahman Kimak Merawang, PRM Nurul Iman Payabenua Mendo Barat, dan Irmas Nurul Huda Gunung Muda Belinyu. Hasil penelitian menunjukkan faktor pendukung seperti budaya desa, dana, fasilitas masjid, latar belakang dan semangat anggota. Sementara faktor penghambat meliputi kesibukan pengurus, semangat menurun, dan jarak ke masjid. Strategi yang diusulkan mencakup pembinaan berkelanjutan, peningkatan kualitas anggota, kerja sama dengan takmir, serta pemanfaatan teknologi digital untuk meningkatkan eksistensi dan efektivitas kegiatan remaja masjid.